Sopa de pollo para el alma durante el embarazo : 101 historias para inspirar y animar a las futuras madres - Canfield, Jack, 1944-; Hernández Clark, Sergio (Aguilar, 2008)
Presents stories aimed at providing the expectant mother with inspiration, insight, and humor as she prepares to give birth.